Bacterial community structure in a latitudinal gradient of lakes: The roles of spatial versus environmental factors - Schiaffino, María Romina (2011)
1.We analysed the latitudinal variation of bacterioplankton in 45 freshwater environments (lakes, shallow lakes and ponds) across a transect of more than 2100km stretching from Argentinean Patagonia (45°S) to Maritime Antarctica (63°S), to determine the factors that mainly determine bacterioplankton community structure. 2.Bacterioplankton community composition (BCC) was assessed by a fingerprinting method (denaturing gradient gel electrophoresis) followed by band sequencing, whereas the abundances of total bacteria and picocyanobacteria were estimated by epifluorescence microscopy. 3.Bacterioplankton community composition was controlled by a combination of spatial (latitude and longitude) and environmental [e.g. phosphate, light diffuse attenuation coefficient (Kd) and dissolved organic carbon] factors. Total bacterioplankton abundance declined with latitude. A multiple regression analysis showed that phosphate, Kd and latitude had significant effects on total bacterioplankton abundance. 4.Of 76 operational taxonomic units identified in the studied lakes, 45 were shared between Patagonian and Antarctic water bodies, 28 were present only in Patagonian lakes and three were restricted to the Antarctic lakes. Significant differences were found in BCC between Patagonia and Antarctica. Among the sequences, 54% were similar (>97% sequence similarity) to others reported from cold habitats elsewhere on the planet (glaciers, high mountain lakes, Arctic). 5.Our results provide new evidence that supports the hypotheses of biogeographic patterns of bacterial assemblages and suggest that both spatial and environmental factors control bacterioplankton community structure.